Water-releasable optical pressure-sensitive adhesive sheet
Patent Information
- Application Number
- JP2023099868
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2025-01-07
AI Technical Summary
【0016】 本発明の水剥離性光学粘着シートは、上記のように、第1水剥離試験での粘着力Fw1が0.5N/10mm以下であり、且つ、高温高湿剥離試験での粘着力Fzが1.0N/10mm以上である。第1水剥離試験での粘着力Fw1が0.5N/10mm以下であることにより、水剥離性光学粘着シートが被着体に貼り合わされた後、水剥離性光学粘着シートにおいて良好な水剥離性を発現させて水リワーク性を確保できる。高温高湿剥離試験での粘着力Fzが1.0N/10mm以上であることにより、水剥離性光学粘着シートが被着体に貼り合わされた後、当該被着体に対する水剥離性光学粘着シートの高温高湿での接着信頼性を確保できる。したがって、本発明の水剥離性光学粘着シートは、水リワーク性を確保しつつ、高温高湿での接着信頼性を確保できる。
Smart Images

Figure 2025000166000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-releasable optical pressure-sensitive adhesive sheet. [Background technology]
[0002] A display panel has a laminated structure including elements such as a pixel panel, a polarizing film, and a cover film. In the manufacturing process of a display panel, for example, an optically transparent adhesive sheet (optical adhesive sheet) is used to bond the elements included in the laminated structure.
[0003] On the other hand, an optical adhesive sheet having water peelability (water peelable optical adhesive sheet) is known. The water peelable optical adhesive sheet is an optical adhesive sheet that can reduce the adhesive force by infiltrating droplets of an aqueous liquid (water droplets, etc.) into the interface between the adherend and the adhesive sheet after being attached to the adherend. After being attached to the adherend, such a water peelable optical adhesive sheet can be easily peeled off from the adherend using water as necessary. For example, in the manufacturing process of a display panel, if a defect (such as misalignment) occurs in the attachment of a water peelable optical adhesive sheet to an adherend, the adhesive sheet can be peeled off from the adherend using water, and a lamination operation can be performed with a replacement optical adhesive sheet (water reworkability). Such a water peelable optical adhesive sheet for display panel use is described, for example, in Patent Document 1 below. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-23679 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 describes a water-releasable optical adhesive sheet containing an acrylic-based polymer and a surfactant. The surfactant is dispersed in a free state in the adhesive sheet. In this adhesive sheet, the presence of the surfactant on the adhesive surface results in water-releasability. However, since the molecular weight of the surfactant is significantly smaller than that of the acrylic-based polymer, the surfactant has a tendency to gradually move to the adhesive surface and its vicinity within the adhesive sheet and become unevenly distributed. In the adhesive sheet of Patent Document 1, a relatively large amount of the surfactant is unevenly distributed on the adhesive surface, which reduces the adhesive strength of the adhesive sheet in a high-temperature and high-humidity environment. The present inventors have obtained such findings regarding the adhesive sheet of Patent Document 1.
[0006] The present invention provides a water-removable optical adhesive sheet that can ensure adhesion reliability at high temperature and high humidity while ensuring water reworkability. [Means for solving the problem]
[0007] The present invention [1] includes a water-peelable optically adhesive sheet having an adhesive strength Fw1 of 0.5 N / 10 mm or less in the first water peeling test described below, and an adhesive strength Fz of 1.0 N / 10 mm or more in the high-temperature, high-humidity peeling test described below.
[0008] First water peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the water-peelable optical adhesive sheet is attached to an alkali glass plate prepared by a float method to obtain a first laminate. Next, the first laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes. Next, the first laminate is left at room temperature for 30 minutes. Next, 20 μL of distilled water is supplied onto the alkali glass plate of the first laminate so that the distilled water contacts one end of the adhesive sheet piece in the length direction at the interface between the alkali glass plate and the adhesive sheet piece. Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling the one end of the adhesive sheet piece in the length direction under conditions of 25°C, relative humidity 50%, peeling angle 180°, and pulling speed 300 mm / min, to measure the adhesive force Fw1.
[0009] High temperature and high humidity peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the water-peelable optical adhesive sheet is attached to an alkali glass plate prepared by a float method to obtain a second laminate. Next, the second laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes. Next, the second laminate is left to stand at room temperature for 30 minutes. Next, the second laminate is subjected to high temperature and high humidity treatment at 60°C, 93% relative humidity, and 15 minutes. Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling one end of the adhesive sheet piece in the length direction under conditions of 60°C, 93% relative humidity, a peel angle of 180°, and a pulling speed of 300 mm / min, to measure the adhesive force Fz.
[0010] The present invention [2] includes the water-peelable optically adhesive sheet according to the above [1], which has a haze of 1% or less.
[0011] The present invention [3] includes the water-peelable optically adhesive sheet according to the above [1] or [2], which does not peel off even after 200,000 flexions in the following flexion test.
[0012] Bend test: First, a laminated film is prepared in which a polyethylene terephthalate film having a thickness of 25 μm and a polyimide film having a thickness of 75 μm are bonded with the water-peelable optical adhesive sheet. Next, the laminated film is heated and pressurized at 50° C., 0.5 MPa, and 15 minutes. Next, a test piece having a width of 25 mm and a length of 100 mm is cut out from the laminated film. Next, in an environment of a temperature of 60° C. and a relative humidity of 95%, the central part of the length direction of the test piece is bent by a planar body no-load U-shaped stretch tester under the conditions that the polyimide film side of the test piece is on the outside of the bend, the bending radius is 1.5 mm, the bending angle is 180°, and the bending speed is 60 rpm.
[0013] The present invention [4] includes the water-peelable optically adhesive sheet according to any one of the above [1] to [3], which has a saturated moisture content of 5 mass % or less at 60° C. and a relative humidity of 95%.
[0014] The present invention [5] includes a water-peelable optical adhesive sheet described in any one of [1] to [4] above, which has an adhesive strength Fw2 in the second water peeling test described below, and the variation rate of the adhesive strength Fw2 relative to the adhesive strength Fw1 is 70% or less.
[0015] Second water peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the water-peelable optical adhesive sheet is attached to an alkali glass plate prepared by a float method to obtain a third laminate. Next, the third laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes. Next, the third laminate is left at room temperature for 72 hours. Next, 20 μL of distilled water is supplied onto the alkali glass plate of the third laminate so that the distilled water contacts one end of the adhesive sheet piece in the length direction at the interface between the alkali glass plate and the adhesive sheet piece. Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling the one end of the adhesive sheet piece in the length direction under conditions of 25°C, relative humidity 50%, peeling angle 180°, and pulling speed 300 mm / min, to measure the adhesive force Fw2. Effect of the Invention
[0016] As described above, the water peelable optical adhesive sheet of the present invention has an adhesive strength Fw1 of 0.5 N / 10 mm or less in the first water peel test, and an adhesive strength Fz of 1.0 N / 10 mm or more in the high temperature and high humidity peel test. By having an adhesive strength Fw1 of 0.5 N / 10 mm or less in the first water peel test, the water peelable optical adhesive sheet can exhibit good water peelability and ensure water reworkability after it is bonded to an adherend. By having an adhesive strength Fz of 1.0 N / 10 mm or more in the high temperature and high humidity peel test, the water peelable optical adhesive sheet can ensure adhesion reliability at high temperature and high humidity to the adherend after it is bonded to an adherend. Therefore, the water peelable optical adhesive sheet of the present invention can ensure adhesion reliability at high temperature and high humidity while ensuring water reworkability. [Brief description of the drawings]
[0017] [Figure 1] 1 is a schematic cross-sectional view of a water-peelable optical adhesive sheet according to one embodiment of the present invention. [Diagram 2] 1 is a schematic diagram of a water peeling test. [Diagram 3] This shows an example of a method for using the water-removable optical adhesive sheet shown in Fig. 1. Fig. 3A shows a step of attaching the water-removable optical adhesive sheet to a first adherend, Fig. 3B shows a step of joining the first adherend and the second adherend via the water-removable optical adhesive sheet, and Fig. 3C shows an aging step. [Figure 4] FIG. 4A shows the test specimen in a flat state in the bending test, and FIG. 4B shows the test specimen in a curved state in the bending test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] As shown in Fig. 1, an adhesive sheet 10 as one embodiment of the water-removable optical adhesive sheet of the present invention has a sheet shape of a predetermined thickness and extends in a direction (plane direction) perpendicular to the thickness direction H. The adhesive sheet 10 has an adhesive surface 11 and an adhesive surface 12 opposite to the adhesive surface 11. Fig. 1 exemplarily shows a state in which release liners L1, L2 are bonded to the adhesive surfaces 11, 12 of the adhesive sheet 10. The release liner L1 is disposed on the adhesive surface 11. The release liner L2 is disposed on the adhesive surface 12.
[0019] The adhesive sheet 10 is an optically transparent adhesive sheet (optical adhesive sheet). The adhesive sheet 10 is an optical adhesive sheet having water releasability. That is, the adhesive sheet 10 is a water releasable optical adhesive sheet that can reduce the adhesive force by infiltrating droplets of an aqueous liquid (water droplets, etc.) into the interface between the adherend and the adhesive sheet 10 after being attached to the adherend. The adhesive sheet 10 is also a water releasable optical adhesive sheet that is disposed, for example, at a light passing portion in a display panel. Examples of the display panel include a liquid crystal panel and an organic EL panel. The display panel has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover film. The adhesive sheet 10 is used, for example, in the manufacturing process of the display panel, to bond elements included in the laminated structure to each other.
[0020] Adhesive sheet 10 has an adhesive strength Fw1 of 0.5 N / 10 mm or less in the first water peel test described below, and an adhesive strength Fz of 1.0 N / 10 mm or more in the high-temperature, high-humidity peel test described below.
[0021] First water peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the adhesive sheet 10 is attached to an alkali glass plate prepared by the float method to obtain a laminate (first laminate) (the adhesive sheet piece is attached to the non-tin side (air side) of the alkali glass plate. The same applies to other peel tests described later). Next, the laminate is heated and pressurized under conditions of 50°C, 0.5 MPa, and 15 minutes. Next, the laminate is left to stand at room temperature for 30 minutes. Next, 20 μL of distilled water is supplied onto the alkali glass plate of the laminate so that the distilled water contacts one end of the adhesive sheet piece in the length direction at the interface between the alkali glass plate and the adhesive sheet piece (water supply step). In this step, as shown in FIG. 2, 20 μL of distilled water 22 is supplied onto the alkali glass plate 21 of the laminate W so that the distilled water 22 contacts one end 10a in the length direction D of the adhesive sheet piece 10A at the interface B between the alkali glass plate 21 and the adhesive sheet piece 10A. Next, the adhesive sheet strip (adhesive sheet strip 10A in FIG. 2) is peeled from the alkali glass plate by pulling one end in the length direction (end 10e in FIG. 2) under conditions of 25° C., 50% relative humidity, a peel angle of 180°, and a pulling speed of 300 mm / min, to measure the adhesive strength. The method of the first water peel test is described more specifically below in the Examples.
[0022] High temperature and high humidity peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the adhesive sheet 10 is attached to an alkaline glass plate prepared by the float method to obtain a laminate (second laminate). Next, the laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes. Next, the laminate is left to stand at room temperature for 30 minutes. Next, the laminate is subjected to high temperature and high humidity treatment at 60°C, 93% relative humidity, and 15 minutes. Next, the adhesive sheet piece is peeled off from the alkaline glass plate by pulling one end of the adhesive sheet piece in the length direction under conditions of 60°C, 93% relative humidity, a peel angle of 180°, and a pulling speed of 300 mm / min, to measure the adhesive strength. The method of the high temperature and high humidity peel test is described more specifically below in relation to the examples.
[0023] As described above, the adhesive sheet 10 has an adhesive strength Fw1 of 0.5 N / 10 mm or less in the first water peeling test, and an adhesive strength Fz of 1.0 N / 10 mm or more in the high temperature and high humidity peeling test. By having an adhesive strength Fw1 of 0.5 N / 10 mm or less in the first water peeling test, the adhesive sheet 10 can exhibit good water peelability and ensure water reworkability after the adhesive sheet 10 is attached to an adherend. By having an adhesive strength Fz of 1.0 N / 10 mm or more in the high temperature and high humidity peeling test, the adhesive sheet 10 can ensure adhesion reliability at high temperature and high humidity to the adherend after the adhesive sheet 10 is attached to the adherend. Therefore, the adhesive sheet 10 can ensure adhesion reliability at high temperature and high humidity while ensuring water reworkability.
[0024] The adhesive strength Fw1 is preferably 0.4 N / 10 mm or less, more preferably 0.3 N / 10 mm or less, and even more preferably 0.25 N / 10 mm or less, from the viewpoint of enhancing the water peelability of the adhesive sheet 10 and realizing good water reworkability. The adhesive strength Fw1 is preferably 0.05 N / 10 mm or more, more preferably 0.1 N / 10 mm or more, and even more preferably 0.15 N / 10 mm or more, from the viewpoint of suppressing lifting and peeling of the adhesive sheet 10 when unintended water adheres to the adhesive sheet 10 on the adherend. Examples of methods for adjusting the adhesive strength Fw1 include selecting the type of base polymer in the adhesive sheet 10, adjusting the molecular weight, adjusting the degree of crosslinking, and adjusting the blending amount. Examples of these adjustment methods include selecting the type of polymerization initiator and crosslinking agent when forming the base polymer and adjusting the blending amount. Examples of methods for adjusting the adhesive strength Fw1 include selecting the type of components other than the base polymer in the adhesive sheet 10 and adjusting the blending amount of the components. The components include an oligomer, a silane coupling agent, and a surfactant. The method of adjusting these is the same as for the adhesive strengths Fz, Fn1, Fn2, and Fw2 described below.
[0025] From the viewpoint of realizing good adhesion reliability of the adhesive sheet 10 under high temperature and high humidity conditions, the adhesive strength Fz is preferably 1.1 N / 10 mm or more, and more preferably 1.2 N / 10 mm or more.
[0026] The pressure-sensitive adhesive sheet 10 has a ratio (Fw1 / Fn1) of adhesive strength Fw1 to adhesive strength Fn1 in the initial peel test described below of preferably 0.20 or less, more preferably 0.15 or less, even more preferably 0.12 or less, and even more preferably 0.10 or less, and is also preferably 0.02 or more, more preferably 0.05 or more. When the ratio (Fw1 / Fn1) is equal to or less than the upper limit, the water peelability of the pressure-sensitive adhesive sheet 10 can be improved to achieve good water reworkability. When the ratio (Fw1 / Fn1) is equal to or more than the lower limit, lifting and peeling of the pressure-sensitive adhesive sheet 10 when unintentional water adheres to the pressure-sensitive adhesive sheet 10 on the adherend can be suppressed.
[0027] Initial peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the adhesive sheet 10 is attached to an alkali glass plate prepared by the float method to obtain a laminate (preparation step). Next, the laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes (heating and pressurizing step). Next, the laminate is left to stand at room temperature for 30 minutes (standing step). Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling one end of the adhesive sheet piece in the length direction under conditions of 25°C, relative humidity of 50%, peeling angle of 180°, and pulling speed of 300 mm / min, to measure the adhesive strength (measurement step). The method of the initial peel test is described more specifically below in relation to the examples.
[0028] The adhesive strength Fn1 is preferably 2 N / 10 mm or more, more preferably 2.5 N / 10 mm or more, even more preferably 2.7 N / 10 mm or more, and is preferably 4.0 N / 10 mm or less, more preferably 3.5 N / 10 mm or less, even more preferably 3.0 N / 10 mm or less. When the adhesive strength Fn1 is equal to or greater than the lower limit, the adhesive reliability of the adhesive sheet 10 to the adherend can be ensured. When the adhesive strength Fn1 is equal to or less than the upper limit, the low adhesive strength Fw1 can be ensured.
[0029] The pressure-sensitive adhesive sheet 10 has an adhesive strength Fw2 in the second water peeling test described below, and the fluctuation rate of the adhesive strength Fw2 relative to the adhesive strength Fw1, expressed by the following formula, is preferably 70% or less, more preferably 60% or less, even more preferably 50% or less, and is also preferably -50% or more, more preferably 0% or more. When the fluctuation rate is equal to or less than the upper limit, the adhesive sheet 10 can ensure stability over time in water peelability and water reworkability. When the fluctuation rate is equal to or more than the lower limit, the adhesive sheet 10 can ensure stability over time in water peelability and water reworkability, while suppressing lifting and peeling of the adhesive sheet 10 when water unintentionally adheres to the adhesive sheet 10 on the adherend.
[0030] Fluctuation rate (%) = [(Fw2-Fw1) / Fw1] x 100
[0031] Second water peel test: The test is the same as the initial peel test except for the following: The resting time in the resting step is 72 hours instead of 30 minutes. After the resting step and before the measurement step, a water supply step is carried out as in the first water peel test.
[0032] The adhesive strength Fw2 is preferably 0.85 N / 10 mm or less, more preferably 0.65 N / 10 mm or less, even more preferably 0.45 N / 10 mm or less, even more preferably 0.38 N / 10 mm or less, and also preferably 0.10 N / 10 mm or more, more preferably 0.15 N / 10 mm or more, even more preferably 0.20 N / 10 mm or more. When the adhesive strength Fw2 is the upper limit or less, the adhesive sheet 10 can ensure stability over time in water peelability and water reworkability. When the adhesive strength Fw2 is the lower limit or more, the adhesive sheet 10 can be prevented from lifting and peeling when unintended water adheres to the adhesive sheet 10 on the adherend.
[0033] The adhesive sheet 10 has an adhesive strength Fn2 in the room temperature peel test described below, and the ratio (Fw2 / Fn2) of the adhesive strength Fw2 to the adhesive strength Fn2 is preferably 0.30 or less, more preferably 0.20 or less, even more preferably 0.15 or less, even more preferably 0.11 or less, and is preferably 0.02 or more, more preferably 0.05 or more. When the ratio (Fw2 / Fn2) is equal to or less than the upper limit, the water peelability of the adhesive sheet 10 can be improved to achieve good water reworkability. When the ratio (Fw2 / Fn2) is equal to or more than the lower limit, lifting and peeling of the adhesive sheet 10 when unintentional water adheres to the adhesive sheet 10 on the adherend can be suppressed.
[0034] Cold peel test: The test was the same as the initial peel test, except that the resting time in the resting step was changed from 30 minutes to 72 hours.
[0035] The adhesive strength Fn2 is preferably 2.0 N / 10 mm or more, more preferably 2.5 N / 10 mm or more, even more preferably 2.7 N / 10 mm or more, and is preferably 4.8 N / 10 mm or less, more preferably 4.4 N / 10 mm or less, even more preferably 4.0 N / 10 mm or less. When the adhesive strength Fn2 is equal to or greater than the lower limit, the adhesive reliability of the adhesive sheet 10 to the adherend can be ensured. When the adhesive strength Fn2 is equal to or less than the upper limit, the low adhesive strength Fw2 can be ensured.
[0036] The haze of the adhesive sheet 10 is preferably 1% or less, more preferably 0.5% or less, even more preferably 0.3% or less, and is, for example, 0.0% or more. When the haze of the adhesive sheet 10 is the above upper limit or less, the adhesive sheet 10 can ensure the transparency required for an optical adhesive sheet for display panel use. The haze of the adhesive sheet 10 can be measured using a haze meter in accordance with JIS K7136 (2000). Examples of haze meters include "NDH2000" manufactured by Nippon Denshoku Industries Co., Ltd. and "HM-150N" manufactured by Murakami Color Research Laboratory Co., Ltd. The method of measuring the haze is specifically described below in relation to the examples.
[0037] In the bending test described below, the adhesive sheet 10 did not peel off even after being bent 200,000 times.
[0038] Bend test: First, a laminated film is prepared in which a polyethylene terephthalate (PET) film having a thickness of 25 μm and a polyimide (PI) film having a thickness of 75 μm are bonded with an adhesive sheet 10. Next, the laminated film is heated and pressurized at 50° C., 0.5 MPa, and 15 minutes. Next, a test piece having a width of 25 mm and a length of 100 mm (PET film / adhesive sheet piece / PI film) is cut out from the laminated film. Next, the test piece is bent at the center in the longitudinal direction by a planar body no-load U-shaped stretch tester under an environment of a temperature of 60° C. and a relative humidity of 95%, with the polyimide film side of the test piece on the outside of the bend, a bending radius of 1.5 mm, a bending angle of 180°, and a bending speed of 60 rpm.
[0039] The saturated moisture content of the adhesive sheet 10 at 60°C and a relative humidity of 95% is preferably 5% by mass or less, more preferably 1% by mass or less, even more preferably 0.50% by mass or less, still more preferably 0.40% by mass or less, even more preferably 0.35% by mass or less, particularly preferably 0.33% by mass or less, and for example, 0.0% by mass or more. When the saturated moisture content of the adhesive sheet 10 is equal to or less than the above upper limit, whitening of the adhesive sheet 10 due to moisture absorption can be suppressed. The method for measuring the saturated moisture content is specifically as described below in the examples.
[0040] The adhesive sheet 10 is a sheet-shaped pressure-sensitive adhesive formed from an adhesive composition. The adhesive sheet 10 (adhesive composition) contains at least a base polymer.
[0041] The base polymer is an adhesive component that imparts adhesiveness to the adhesive sheet 10. Examples of base polymers include acrylic polymers, silicone polymers, polyester polymers, polyurethane polymers, polyamide polymers, polyvinyl ether polymers, vinyl acetate / vinyl chloride copolymers, modified polyolefin polymers, epoxy polymers, fluoropolymers, and rubber polymers. The base polymers may be used alone or in combination of two or more. From the viewpoint of ensuring good transparency and adhesiveness in the adhesive sheet 10, the base polymer is preferably an acrylic polymer. The acrylic polymer is a copolymer of monomer components containing 50% or more by mass of (meth)acrylic acid ester. "(Meth)acrylic" means acrylic and / or methacrylic.
[0042] In this embodiment, the acrylic polymer is a polymerized product obtained by photopolymerization of a polymerizable component including a monofunctional monomer and a polyfunctional polymerizable compound as a crosslinking agent. Photopolymerization is a polymerization method in which a polymerization reaction of a polymerizable component is advanced by irradiation with active energy rays such as ultraviolet rays. The acrylic polymer is, for example, a polymerized product obtained by photopolymerization of a partial polymerized product (a mixture of a polymerized product of a monofunctional monomer and an unreacted monofunctional monomer) of a monofunctional monomer and a polyfunctional polymerizable compound.
[0043] Such an acrylic polymer includes a photopolymerized polymer (first photopolymerized polymer) having a photocrosslinked structure. The photocrosslinked structure is a structure in which a linear structure of units derived from a monofunctional monomer is crosslinked by a unit derived from a crosslinking agent. The base polymer may include a photopolymerized polymer (second photopolymerized polymer) that does not have such a photocrosslinked structure. The second photopolymerized polymer is a polymer of a monofunctional monomer.
[0044] The monofunctional monomer preferably contains a monofunctional (meth)acrylic acid alkyl ester, and more preferably contains a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 20 carbon atoms. The (meth)acrylic acid alkyl ester may have a linear or branched alkyl group, or may have a cyclic alkyl group (alicyclic alkyl group).
[0045] Examples of linear or branched (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and isooctyl (meth)acrylate.
[0113] Examples of suitable acrylates include but are not limited to, but are not limited to, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, and nonadecyl (meth)acrylate.
[0046] Examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl ester, (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring, and (meth)acrylic acid alkyl ester having a tricyclic or higher aliphatic hydrocarbon ring. Examples of the (meth)acrylic acid cycloalkyl ester include (meth)acrylic acid cyclopentyl, (meth)acrylic acid cyclohexyl, (meth)acrylic acid cycloheptyl, and (meth)acrylic acid cyclooctyl. Examples of the (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring include (meth)acrylic acid isobornyl. Examples of (meth)acrylic acid alkyl esters having three or more aliphatic hydrocarbon rings include dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate.
[0047] The monofunctional (meth)acrylic acid alkyl ester may be used alone or in combination of two or more kinds. The monofunctional (meth)acrylic acid alkyl ester is preferably an acrylic acid alkyl ester having an alkyl group having 3 to 12 carbon atoms, and more preferably at least one selected from the group consisting of n-butyl acrylate (BA) and n-octyl acrylate (NOAA).
[0048] The proportion of monofunctional (meth)acrylic acid alkyl ester in the polymerizable component is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and more preferably 85% by mass or more, from the viewpoint of appropriately exhibiting basic properties such as adhesiveness in the adhesive sheet 10. This proportion is, for example, 99% by mass or less.
[0049] The monofunctional monomer may include a copolymerizable monomer that can be copolymerized with the monofunctional (meth)acrylic acid alkyl ester. The copolymerizable monomer may include, for example, a polar group-containing monomer. The polar group-containing monomer may include, for example, a hydroxy group-containing monomer, a carboxy group-containing monomer, and a monomer having a nitrogen atom-containing ring. The polar group-containing monomer is useful for modifying the acrylic polymer, such as ensuring the cohesive force of the acrylic polymer.
[0050] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl group-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (2HEA) and 4-hydroxybutyl acrylate (4HBA).
[0051] The proportion of the hydroxy group-containing monomer in the polymerizable component is preferably 1 mass % or more, more preferably 5 mass % or more, and even more preferably 7 mass % or more, from the viewpoint of ensuring the cohesive strength of the pressure-sensitive adhesive sheet 10. From the viewpoint of adjusting the polarity of the acrylic polymer (related to the compatibility between the various additive components in the pressure-sensitive adhesive sheet 10 and the acrylic polymer), this proportion is preferably 30 mass % or less, more preferably 20 mass % or less, and even more preferably 15 mass % or less.
[0052] Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.
[0053] From the viewpoint of avoiding the risk of corrosion of the adherend by acid, the proportion of the carboxyl group-containing monomer in the polymerizable component is preferably 3 mass % or less, more preferably 1 mass % or less, even more preferably 0.5 mass % or less, and even more preferably 0.1 mass % or less.
[0054] Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, and acryloylmorpholine. The monomer having a nitrogen atom-containing ring is preferably at least one selected from the group consisting of N-vinyl-2-pyrrolidone (NVP) and acryloylmorpholine (ACMO).
[0055] The proportion of the monomer having a nitrogen atom-containing ring in the polymerizable component is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, from the viewpoints of ensuring the cohesive strength of the pressure-sensitive adhesive sheet and the adhesive strength of the pressure-sensitive adhesive sheet to the adherend. The proportion is preferably 10% by mass or less, more preferably 5% by mass or less, from the viewpoints of adjusting the glass transition temperature of the acrylic polymer and adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet with the acrylic polymer).
[0056] Examples of the polyfunctional polymerizable compound include polyfunctional monomers containing two or more ethylenically unsaturated double bonds in one molecule. Examples of the polyfunctional monomer include polyfunctional (meth)acrylates. Examples of the polyfunctional (meth)acrylates include bifunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional or higher polyfunctional (meth)acrylates.
[0057] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerin di(meth)acrylate, neopentyl glycol di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, dicyclopentenyl diacrylate, di(meth)acryloyl isocyanurate, and ethoxylated bisphenol A diacrylate (BPAEODE).
[0058] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.
[0059] Examples of tetrafunctional or higher polyfunctional (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol pentaacrylate, and dipentaerythritol hexa(meth)acrylate.
[0060] The polyfunctional polymerizable compound may be used alone or in combination of two or more kinds. The polyfunctional polymerizable compound is preferably dipentaerythritol hexaacrylate (DPHA).
[0061] The ratio of the polyfunctional polymerizable compound in the polymerizable component is preferably 0.01% by mass or more, more preferably 0.04% by mass or more, even more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, even more preferably 0.8% by mass or more, and also preferably 2% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1.2% by mass or less. When the amount of the polyfunctional polymerizable compound is equal to or more than the above lower limit, the adhesive sheet 10 can ensure cohesive force and can ensure adhesion reliability after being attached to an adherend. When the amount of the polyfunctional polymerizable compound is equal to or less than the above upper limit, the wettability of the adhesive sheet 10 to the adherend can be ensured, and the adhesive sheet 10 immediately after being attached to the adherend can ensure both adhesive force and water reworkability.
[0062] In this embodiment, the acrylic polymer is formed by photopolymerization of the polymerizable components. The polymerizable components (including a monofunctional monomer and a polyfunctional polymerizable compound for introducing a crosslinked structure) may be polymerized in one step or in multiple steps. In the multistep polymerization method, first, a prepolymer composition containing a partial polymer (a mixture of a polymer of a monofunctional monomer and an unreacted monofunctional monomer) is prepared by polymerizing a monofunctional monomer (preliminary polymerization). Next, a polyfunctional polymerizable compound is added as a crosslinking agent to the prepolymer composition, and then a polymerization reaction is allowed to proceed in a reaction system containing the partial polymer and the polyfunctional polymerizable compound (main polymerization). In the photopolymerization, a photopolymerization initiator may be used.
[0063] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator.
[0064] Examples of the radical photopolymerization initiator include an acylphosphine oxide photopolymerization initiator, a benzoin ether photopolymerization initiator, an acetophenone photopolymerization initiator, an α-ketol photopolymerization initiator, an aromatic sulfonyl chloride photopolymerization initiator, a photoactive oxime photopolymerization initiator, a benzoin photopolymerization initiator, a benzyl photopolymerization initiator, a benzophenone photopolymerization initiator, a ketal photopolymerization initiator, and a thioxanthone photopolymerization initiator.
[0065] Examples of the acylphosphine oxide photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-1,2-diphenylethan-1-one. Examples of acetophenone photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of α-ketol photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin photopolymerization initiators include benzoin. Examples of benzyl photopolymerization initiators include benzyl. Benzophenone photoinitiators include, for example, benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and polyvinylbenzophenone. Ketal photoinitiators include, for example, benzyl dimethyl ketal. Thioxanthone photoinitiators include, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.The photopolymerization initiator may be used alone or in combination of two or more kinds. The photopolymerization initiator is preferably at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-1,2-diphenylethan-1-one, and 1-hydroxycyclohexyl phenyl ketone.
[0066] The amount of the photopolymerization initiator is preferably 0.03 parts by mass or more, more preferably 0.06 parts by mass or more, even more preferably 0.08 parts by mass or more, and also preferably 0.3 parts by mass or less, more preferably 0.2 parts by mass or less, per 100 parts by mass of the polymerizable component. When the amount of the photopolymerization initiator is equal to or more than the lower limit, a crosslinked network with sufficient crosslinking density can be formed in the acrylic polymer, and the adhesive strength of the adhesive sheet 10 can be ensured. When the amount of the photopolymerization initiator is equal to or less than the upper limit, the occurrence of multiple polymerization initiation points during photopolymerization can be suppressed, and a long-distance and continuous crosslinked network can be formed in the acrylic polymer. When the acrylic polymer is photopolymerized by preliminary polymerization and main polymerization, a photopolymerization initiator may be added after the preliminary polymerization and during the main polymerization. In that case, the amount of the photopolymerization initiator in the preliminary polymerization is preferably 0.03 parts by mass or more, more preferably 0.06 parts by mass or more, even more preferably 0.08 parts by mass or more, and also preferably 0.3 parts by mass or less, more preferably 0.2 parts by mass or less, per 100 parts by mass of the monofunctional monomer. The amount of photopolymerization initiator (additional photopolymerization initiator) added during the main polymerization is preferably 0.01 parts by mass or more, more preferably 0.015 parts by mass or more, and preferably 0.03 parts by mass or less, more preferably 0.025 parts by mass or less, per 100 parts by mass of the polymerizable component. When the amount of the photopolymerization initiator is equal to or less than the upper limit, it is possible to suppress a decrease in the water wettability of the adhesive sheet 10 caused by low molecular weight components in the adhesive sheet 10. In the adhesive sheet 10, suppressing a decrease in water wettability helps ensure water reworkability.
[0067] The weight average molecular weight of the base polymer is preferably 500,000 or more, more preferably 800,000 or more, even more preferably 1,000,000 or more, and even more preferably 1,500,000 or more, from the viewpoint of ensuring the cohesive force in the pressure-sensitive adhesive sheet 10. The weight average molecular weight of the base polymer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.
[0068] The glass transition temperature Tg1 of the base polymer is preferably 0° C. or lower, more preferably −20° C. or lower, even more preferably −40° C. or lower, and even more preferably −45° C. or lower, from the viewpoint of ensuring sufficient softness in the pressure-sensitive adhesive sheet 10. The glass transition temperature Tg1 is, for example, −80° C. or higher.
[0069] The glass transition temperature of the base polymer may be determined by the following Fox formula (theoretical value). The Fox formula is a relational expression between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of a polymer, Wi represents the weight fraction of a monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of a homopolymer formed from the monomer i. The glass transition temperature of a homopolymer may be determined by a literature value. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999) and "New Polymer Library 7: Introduction to Synthetic Resins for Paints" (Kyozo Kitaoka, Polymer Publishing Association, 1995). On the other hand, the glass transition temperature of a homopolymer of a monomer may be determined by a method specifically described in JP-A-2007-51271.
[0070] Fox formula 1 / (273+Tg)=Σ[Wi / (273+Tgi)]
[0071] The pressure-sensitive adhesive sheet 10 may contain other components, such as a silane coupling agent, an ultraviolet absorbing agent, an antioxidant, and an anti-rust agent.
[0072] Examples of the silane coupling agent include silane coupling agents containing an epoxy group. Examples of the silane coupling agent containing an epoxy group include 3-glycidoxydialkyldialkoxysilane and 3-glycidoxyalkyltrialkoxysilane. Examples of the 3-glycidoxydialkyldialkoxysilane include 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane. Examples of the 3-glycidoxyalkyltrialkoxysilane include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. As the silane coupling agent, preferably, 3-glycidoxyalkyltrialkoxysilane is used, and more preferably, 3-glycidoxypropyltrimethoxysilane is used. The silane coupling agent may be used alone or in combination of two or more kinds. The proportion of the silane coupling agent in the pressure-sensitive adhesive sheet 10 is preferably 3 mass % or less, more preferably 1 mass % or less, even more preferably 0.1 mass % or less, and particularly preferably 0.0 mass %. Such a configuration is preferable for suppressing the adhesive strength of the pressure-sensitive adhesive sheet 10 to glass and achieving good water peelability.
[0073] The adhesive sheet 10 preferably does not substantially contain a free surfactant. The more free surfactant there is in the adhesive sheet, the lower the adhesive strength of the adhesive sheet in a high-temperature, high-humidity environment. From the viewpoint of ensuring the adhesive strength of the adhesive sheet 10 in a high-temperature, high-humidity environment, the proportion of surfactant in the adhesive sheet 10 is preferably 0.05% by mass or less, more preferably 0.03% by mass or less, even more preferably 0.01% by mass or less, and particularly preferably 0.00% by mass. The adhesive sheet 10 preferably does not substantially contain a free surfactant and a silane coupling agent.
[0074] The pressure-sensitive adhesive sheet 10 preferably does not substantially contain an oligomer such as an acrylic oligomer. The proportion of the oligomer in the pressure-sensitive adhesive sheet 10 is preferably 3 mass % or less, more preferably 1 mass % or less, even more preferably 0.1 mass %, and particularly preferably 0.0 mass %. The pressure-sensitive adhesive sheet 10 preferably does not substantially contain a surfactant, a silane coupling agent, or an oligomer in a free state.
[0075] From the viewpoint of ensuring sufficient adhesion to the adherend, the thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 μm or more, more preferably 20 μm or more. From the viewpoint of the ease of handling and cutting of the pressure-sensitive adhesive sheet 10, the thickness of the pressure-sensitive adhesive sheet 10 is preferably 500 μm or less, more preferably 400 μm or less, even more preferably 300 μm or less, even more preferably 200 μm or less, and even more preferably 150 μm or less.
[0076] The total light transmittance of the pressure-sensitive adhesive sheet 10 is preferably 90% or more, more preferably 92% or more, and is, for example, 100% or less. When the total light transmittance of the pressure-sensitive adhesive sheet 10 is equal to or more than the above lower limit, the pressure-sensitive adhesive sheet 10 can ensure the transparency required for an optical pressure-sensitive adhesive sheet for use in a display panel. The total light transmittance of the pressure-sensitive adhesive sheet 10 is, for example, 100% or less. The total light transmittance can be measured in accordance with JIS K 7375 (2008).
[0077] The release liner L1 is, for example, a transparent resin film having flexibility. Examples of the material of the release liner L1 include polyester resin, polyolefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, cellulose resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). From the viewpoints of transparency and strength, the material of the release liner L1 is preferably a polyester resin, and more preferably PET. The surface of the release liner L1 on the side of the pressure-sensitive adhesive sheet 10 is preferably subjected to a release treatment with a release treatment agent. Examples of the release treatment include a silicone release treatment, a long-chain alkyl acrylate release treatment, and a fluorine release treatment.
[0078] The release liner L2 is a flexible, transparent resin film. Examples of materials for the release liner L2 include the materials mentioned above for the release liner L1. From the viewpoints of transparency and strength, the material for the release liner L2 is preferably a polyester resin, more preferably PET. The surface of the release liner L2 on the side of the PSA sheet 10 is preferably release-treated with a release treating agent. Examples of the release treatment include the release treatments mentioned above for the release liner L1.
[0079] The adhesive sheet 10 can be produced, for example, as follows.
[0080] First, the pressure-sensitive adhesive composition is prepared. Specifically, a mixture (liquid) containing the monofunctional monomer and the photopolymerization initiator is irradiated with ultraviolet light to photopolymerize a portion of the monofunctional monomer in the mixture to obtain a prepolymer composition. Examples of light sources for ultraviolet light irradiation include ultraviolet LED lights, high-pressure mercury lamps, black light lamps, and metal halide lamps. In addition, in the ultraviolet light irradiation, a wavelength cut filter for cutting a portion of the wavelength range of the light emitted from the light source may be used as necessary. In the ultraviolet light irradiation, the illuminance is, for example, 5 to 200 mW / cm. 2 m, and the cumulative irradiation dose is, for example, 100 to 5000 mJ / cm 2 It is preferable to continue the ultraviolet irradiation until the viscosity of the composition reaches about 15 to 25 Pa·s. This viscosity is a value measured by a B-type viscometer under the conditions of rotor No. 5, rotor rotation speed of 10 rpm, and temperature of 30°C. The prepolymer composition contains a photopolymerized product of a monofunctional monomer (the second photopolymerized polymer) and a monofunctional monomer (residual monomer) that has not undergone a polymerization reaction. In addition, the prepolymer composition does not contain a solvent. Next, a multifunctional polymerizable compound and, if necessary, other components are added to the prepolymer composition. Examples of the other components include an additional photopolymerization initiator, a silane coupling agent, and an antioxidant. This results in a pressure-sensitive adhesive composition. The pressure-sensitive adhesive composition does not contain a solvent, and is therefore a solvent-free pressure-sensitive adhesive composition.
[0081] Next, a pressure-sensitive adhesive composition is applied onto the release liner L1 to form a coating film, and then a release liner L2 is laminated onto the coating film on the release liner L1. Examples of methods for applying the pressure-sensitive adhesive composition include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating.
[0082] Next, the coating film between the release liners L1 and L2 is irradiated with ultraviolet light to photocure it, forming a pressure-sensitive adhesive layer. The ultraviolet light irradiation causes a polymerization reaction in the coating film in a reaction system containing the above-mentioned residual monomer and a polyfunctional polymerizable compound, and a first photopolymerized polymer having a photocrosslinked structure is formed. Thereafter, the pressure-sensitive adhesive layer may be dried by heating. The drying temperature is, for example, 80°C to 150°C. The drying time is, for example, 30 seconds to 10 minutes. The drying process allows the unreacted monomer in the pressure-sensitive adhesive layer to be volatilized and removed.
[0083] In this manner, adhesive sheet 10 can be manufactured in which adhesive surfaces 11, 12 are covered and protected by release liners L1, L2. Release liners L1, L2 are peeled off from adhesive sheet 10 as necessary when adhesive sheet 10 is to be used.
[0084] 3A to 3C show an example of a method of using the adhesive sheet 10. FIG.
[0085] In this method, first, as shown in Fig. 3A, the adhesive sheet 10 is attached to one surface in the thickness direction H of a member 31 (first adherend) (attaching step). Examples of the member 31 include a pixel panel and a polarizing film in a display panel. Through this step, the adhesive sheet 10 for bonding to another member is provided on the member 31.
[0086] In this step, if a defect (such as misalignment) occurs in the bonding of the adhesive sheet 10 to the member 31, the adhesive sheet 10 can be appropriately peeled off from the member 31 using water. For example, by infiltrating water droplets into the interface between the member 31 and the adhesive sheet 10, the adhesive strength of the adhesive sheet 10 can be reduced, and then the adhesive sheet 10 can be easily peeled off from the member 31. After peeling, the bonding step to the member 31 can be carried out again using a replacement adhesive sheet 10 (rework).
[0087] 3B, the member 31 and a member 32 (second adherend) are joined via the adhesive sheet 10 on the member 31 (joining step). An example of the member 32 is a cover film in a display panel.
[0088] Next, as shown in Fig. 3C, the adhesive sheet 10 between the members 31 and 32 is aged (aging step). This step enhances the bonding strength between the adhesive sheet 10 and the members 31 and 32. The aging temperature is, for example, 20°C to 160°C. The aging time is, for example, 1 minute to 21 days. When autoclaving (heat and pressure treatment) is used for aging, the temperature is, for example, 30°C to 80°C, the pressure is, for example, 0.1 to 0.8 MPa, and the treatment time is, for example, 15 minutes or longer.
[0089] According to the adhesive sheet 10, after the bonding step or the aging step, the bonded state between the members 31, 32 can be easily released by using water as necessary.
[0090] By allowing water droplets to penetrate into the interface between the member 31 and the adhesive sheet 10, the adhesive force of the adhesive sheet 10 to the member 31 is reduced, and then the member 32 with the adhesive sheet 10 can be easily separated from the member 31. Thereafter, for example, a replacement member 32 with the adhesive sheet 10 can be bonded to the member 31 via the adhesive sheet 10.
[0091] Alternatively, by allowing water droplets to penetrate into the interface between the member 32 and the adhesive sheet 10, the adhesive force of the adhesive sheet 10 to the member 32 is reduced, and then the member 31 with the adhesive sheet 10 can be easily separated from the member 32. Thereafter, for example, a replacement member 31 with the adhesive sheet 10 can be bonded to the member 32 via the adhesive sheet 10.
[0092] According to adhesive sheet 10, the adhesive strength Fw1 in the first water peel test is 0.5 N / 10 mm or less, and therefore, for example, the above-mentioned rework is possible. EXAMPLES
[0093] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".
[0094] Example 1 Preparation of Prepolymer Composition In a flask, 20 parts by mass of n-butyl acrylate (BA), 70 parts by mass of n-octyl acrylate (NOAA), 8 parts by mass of 4-hydroxybutyl acrylate (4HBA), and 2 parts by mass of N-vinyl-2-pyrrolidone (NVP) were mixed with 0.05 parts by mass of a first photopolymerization initiator (product name "Irgacure 819", bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, manufactured by BASF Japan Ltd.) and 0.05 parts by mass of a second photopolymerization initiator (product name "Irgacure 184", 1-hydroxycyclohexyl phenyl ketone, manufactured by BASF Japan Ltd.), and then the mixture was irradiated with ultraviolet light under a nitrogen atmosphere to polymerize a part of the monomer components in the mixture, thereby obtaining a prepolymer composition with a polymerization rate of about 10%. This prepolymer composition is a partial polymer containing a photopolymerized product (photopolymerized polymer P1a) and a monomer component (residual monomer) that has not undergone a polymerization reaction.
[0095] Preparation of Pressure-Sensitive Adhesive Composition Next, 100 parts by mass of the prepolymer composition and 0.045 parts by mass of dipentaerythritol hexaacrylate (trade name "KAYARAD DPHA", manufactured by Nippon Kayaku Co., Ltd.) as a polyfunctional polymerizable compound were mixed to prepare a pressure-sensitive adhesive composition.
[0096] <Preparation of Adhesive Sheet> Next, a pressure-sensitive adhesive composition was applied onto the release-treated surface of a first release liner (product name "Diafoil MRF", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side to form a coating film. Next, the release-treated surface of a second release liner (product name "Diafoil MRN", thickness 38 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached onto the coating film on the first release liner. Next, the coating film between the release liners was irradiated with ultraviolet light from the second release liner side, and the coating film was photocured to form a 50 μm-thick pressure-sensitive adhesive layer (ultraviolet light irradiation process). For ultraviolet light irradiation, a black light lamp (manufactured by Toshiba) was used as the light source, and the illuminance was set to 5.0 mW / cm. 2 The cumulative irradiation dose was 1500 mJ / cm 2 In the ultraviolet irradiation step, a photopolymerization reaction proceeds in the coating film in a reaction system containing the above-mentioned residual monomer and the polyfunctional polymerizable compound, and a photopolymerized polymer P1b having a photocrosslinked structure is formed. In addition, since the photopolymerization reaction proceeds around the above-mentioned photopolymerized polymer P1a, the photopolymerized polymer P1b is formed around the photopolymerized polymer P1a. The pressure-sensitive adhesive layer formed in this step contains such photopolymerized polymer P1a and photopolymerized polymer P1b as base polymers.
[0097] Next, after peeling the first release liner from the adhesive layer, the adhesive layer on the second release liner was dried in a hot air oven at 130°C for 3 minutes. This caused the unreacted monomer in the adhesive layer to volatilize and be removed. Then, after cooling at room temperature, the release-treated surface of a third release liner (product name "Diafoil MRF", thickness 38μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached to the adhesive layer on the second release liner.
[0098] In this manner, the pressure-sensitive adhesive sheet with release liner of Example 1 (second release liner / pressure-sensitive adhesive sheet (thickness 50 μm) / third release liner) was produced.
[0099] Example 2 The pressure-sensitive adhesive sheet with release liner of Example 2 was produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, the amount of DPHA was 1.1 parts by mass, and 0.02 parts by mass of a photopolymerization initiator (Irgacure 819) was further added.
[0100] Comparative Example 1 An adhesive sheet with a release liner of Comparative Example 1 was produced in the same manner as the adhesive sheet with a release liner of Example 1, except for the following: In preparing the adhesive composition, 1.5 parts by mass of the following acrylic oligomer and 0.02 parts by mass of a photopolymerization initiator (Irgacure 819) were further added.
[0101] Preparation of Acrylic Oligomer First, in a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, a mixture containing 60 parts by mass of dicyclopentanyl methacrylate (DCPMA), 40 parts by mass of methyl methacrylate (MMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred under a nitrogen atmosphere at 70°C for 1 hour. Next, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted under a nitrogen atmosphere at 70°C for 2 hours and then at 80°C for 2 hours (polymerization reaction). Next, the reaction solution was heated at 130°C to volatilize and remove toluene, the chain transfer agent, and unreacted monomers. This resulted in a solid acrylic oligomer. The weight average molecular weight of this acrylic oligomer was 5100, and the glass transition temperature was 130°C.
[0102] Comparative Example 2 An adhesive sheet with a release liner of Comparative Example 2 was produced in the same manner as the adhesive sheet with a release liner of Example 1, except for the following: In preparing the adhesive composition, the amount of DPHA was 1.1 parts by mass, and 1.5 parts by mass of the acrylic oligomer, 0.02 parts by mass of a photopolymerization initiator (Irgacure 819), and 0.5 parts by mass of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were further added.
[0103] Comparative Example 3 A release-lined pressure-sensitive adhesive sheet of Comparative Example 3 was produced in the same manner as the release-lined pressure-sensitive adhesive sheet of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, 1.5 parts by mass of the acrylic oligomer, 0.02 parts by mass of a photopolymerization initiator (Irgacure 819), and 0.5 parts by mass of a silane coupling agent (KBM-403) were further added.
[0104] Comparative Example 4 A pressure-sensitive adhesive sheet with a release liner of Comparative Example 4 was produced in the same manner as the pressure-sensitive adhesive sheet with a release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, 1.5 parts by mass of the acrylic oligomer and 0.04 parts by mass of a photopolymerization initiator (Irgacure 819) were further added.
[0105] Comparative Example 5 An adhesive sheet with a release liner of Comparative Example 5 was produced in the same manner as the adhesive sheet with a release liner of Example 1, except for the following: In preparing the adhesive composition, 0.1 part by mass of a surfactant (product name "Rheodol TW-L120", manufactured by Kao Corporation), 0.04 part by mass of an additional photopolymerization initiator (Irgacure 819), and 0.5 part by mass of a silane coupling agent (KBM-403) were further blended.
[0106] Comparative Example 6 The pressure-sensitive adhesive sheet with release liner of Comparative Example 6 was produced in the same manner as the pressure-sensitive adhesive sheet with release liner of Example 1, except for the following: In preparing the pressure-sensitive adhesive composition, 0.04 part by mass of a photopolymerization initiator (Irgacure 819) was further added.
[0107] Haze For each of the pressure-sensitive adhesive sheets of Examples 1 and 2 and Comparative Examples 1 to 6, the haze was measured as follows.
[0108] First, a sample for measurement was prepared. Specifically, after peeling off the third release liner from the adhesive sheet, the exposed surface of the adhesive sheet was attached to an alkali-free glass plate (thickness 0.8-1.0 mm, total light transmittance 92%, haze 0.4%, manufactured by Matsunami Glass Co., Ltd.). Next, the second release liner was peeled off from the adhesive sheet on the glass plate. This resulted in a sample for measurement. Next, the haze of the sample was measured in accordance with JIS K7136 (2000) using a haze meter "HM-150N" manufactured by Murakami Color Research Laboratory Co., Ltd. In this measurement, the sample was placed in the haze meter so that light was irradiated from the alkali-free glass plate side of the sample. In addition, in this measurement, the measurement results obtained by measuring only the alkali-free glass plate under the same conditions were used as a baseline. The haze of the adhesive sheet thus obtained is shown in Table 1.
[0109] <Saturated moisture content> For each of the pressure-sensitive adhesive sheets of Examples 1 and 2 and Comparative Examples 1 to 6, the saturated moisture content was measured as follows.
[0110] First, a piece of adhesive sheet with a release liner (1 cm x 5 cm) was cut out from the adhesive sheet with a release liner. The piece of adhesive sheet with a release liner was then stored for 48 hours under conditions of a temperature of 60°C and a relative humidity of 95%. Next, one release liner was removed from the piece of adhesive sheet with a release liner by peeling, and the piece of adhesive sheet exposed by the peeling was attached to an aluminum foil that had been weighed in advance. Next, the other release liner was removed from the piece of adhesive sheet. This resulted in a sample. Next, the sample (aluminum foil / adhesive sheet piece) was weighed. Next, the moisture content of the adhesive sheet piece in the sample was measured under the following conditions by Karl Fischer coulometric titration using a moisture meter (product name "CA-310 type", manufactured by Nitto Seiko Analytech Co., Ltd.) equipped with a heating vaporizer (product name "VA-300 type", manufactured by Nitto Seiko Analytech Co., Ltd.). The value is shown in Table 1 as the saturated moisture content.
[0111] [Conditions for moisture content measurement] Anolyte: Aquamicron AKX (Mitsubishi Chemical) Catholyte: Aquamicron CXU (Mitsubishi Chemical) Heat vaporization temperature: 150℃
[0112] <Initial peeling test> An initial peel test was carried out on each of the pressure-sensitive adhesive sheets of Examples 1 and 2 and Comparative Examples 1 to 6 to measure the adhesive strength Fn1. Specifically, the test was performed as follows.
[0113] Preparation steps: First, the third release liner was peeled off from the adhesive sheet with release liner (second release liner / adhesive sheet / third release liner). Next, the adhesive sheet exposed by this was attached to a polyethylene terephthalate (PET) film (product name "Lumirror S10", thickness 50 μm, manufactured by Toray) whose surface had been plasma-treated. This resulted in a laminated film. In the plasma treatment, a plasma irradiation device (product name "AP-TO5", manufactured by Sekisui Kogyo Co., Ltd.) was used, and the voltage was set to 160 V, the frequency was set to 10 kHz, and the treatment speed was set to 5000 mm / min. In the lamination, the adhesive sheet was pressed against the PET film by moving a 2 kg hand roller back and forth once in an environment of 25°C. Next, a laminated film piece with a width of 10 mm and a length of 100 mm was cut out from the laminated film. This laminated film has a PET film, an adhesive sheet piece, and a second release liner in this order in the thickness direction. Next, the second release liner was peeled off from the adhesive sheet piece on the PET film, and the adhesive sheet piece (width 10 mm × length 100 mm) exposed thereby was then attached to the non-tin surface (air surface) of an alkali glass plate prepared by the float method to obtain a laminate.
[0114] Heat and pressure step: Next, the laminate was subjected to a heat and pressure treatment under conditions of 50° C., 0.5 MPa and 15 minutes, thereby causing the adhesive sheet piece to be pressure-bonded to the alkaline glass plate.
[0115] Settling step: The laminate was then allowed to stand at room temperature for 30 minutes.
[0116] Measurement steps: Next, a 180° peel test was performed to peel the adhesive sheet piece from the alkali glass plate in the laminate, and the force required for peeling (peeling force) was measured. A tensile tester (product name "Autograph AG-50NX plus", manufactured by Shimadzu Corporation) was used for this measurement. Specifically, in this measurement, the adhesive sheet piece was peeled from the alkali glass plate by pulling one end in the length direction of the adhesive sheet piece on the alkali glass plate under the conditions of 25°C, 50% relative humidity, 180° peeling angle, and 300 mm / min pulling speed (first condition), and the adhesive force was measured. The peel length was set to 50 mm, and the average value of the measured peel forces was taken as the adhesive force. The adhesive force Fn1 (N / 10 mm) measured in the measurement step of the initial peel test is shown in Table 1.
[0117] <First water peeling test> A first water peeling test was carried out to measure adhesive strength Fw1 for each of the pressure-sensitive adhesive sheets of Examples 1 and 2 and Comparative Examples 1 to 6. The first water peeling test was the same as the initial peeling test described above, except that the water supplying step described below was carried out after the standing step and before the measurement step. The adhesive strengths Fw1 (N / 10 mm) measured in the measurement step of the first water peeling test are shown in Table 1. The ratio of adhesive strength Fw1 to adhesive strength Fn1 (Fw1 / Fn1) is also shown in Table 1.
[0118] Water supply steps: After the standing step, 20 μL of distilled water was supplied onto the alkaline glass plate of the laminate such that the distilled water was in contact with one end in the longitudinal direction of the adhesive sheet piece at the interface between the alkaline glass plate and the adhesive sheet piece.
[0119] <Room temperature peel test> A room temperature peel test was carried out to measure the adhesive strength Fn2 for each of the pressure-sensitive adhesive sheets of Examples 1 and 2 and Comparative Examples 1 to 6. The room temperature peel test was the same as the initial peel test described above, except that in the resting step, the laminate was left at room temperature for 72 hours. The adhesive strength Fn2 (N / 10 mm) measured in the measurement step of the room temperature peel test is shown in Table 1.
[0120] <Second water peeling test> A second water peeling test was carried out on each of the pressure-sensitive adhesive sheets of Examples 1 and 2 and Comparative Examples 1 to 6 to measure the adhesive strength Fw2. The second water peeling test was the same as the first water peeling test described above, except that in the standing step, the laminate was left to stand at room temperature for 72 hours. The adhesive strength Fw2 (N / 10 mm) measured in the measurement step of the second water peeling test is shown in Table 1. The ratio (Fw2 / Fn2) of the adhesive strength Fw2 to the adhesive strength Fn2 is also shown in Table 1. The variation rate (%) of the adhesive strength Fw2 to the adhesive strength Fw1 is also shown in Table 1. This variation rate is calculated by the following formula.
[0121] Fluctuation rate (%) = [(Fw2-Fw1) / Fw1] x 100
[0122] <High temperature and high humidity peeling test> A high-temperature, high-humidity peel test was carried out on each of the pressure-sensitive adhesive sheets of Examples 1 and 2 and Comparative Examples 1 to 6 to measure the adhesive strength Fz. The high-temperature, high-humidity peel test was the same as the initial peel test except for the following. After the leaving step and before the measurement step, the following high-temperature, high-humidity treatment step was carried out. In the measurement step, instead of the first condition described above, a 180° peel test was carried out under conditions (second conditions) of 60°C, relative humidity 93%, a peel angle of 180°, and a pulling speed of 300 mm / min. The adhesive strengths Fz (N / 10 mm) measured in the measurement step of the high-temperature, high-humidity peel test are shown in Table 1.
[0123] Humidity and heat treatment steps: The laminate after the standing step was subjected to high-temperature and high-humidity treatment under conditions of 60° C., relative humidity of 93%, and for 15 minutes.
[0124] <Bending test> For each of the pressure-sensitive adhesive sheets of Examples 1 and 2 and Comparative Examples 1 to 6, a bending test was performed as follows.
[0125] First, the third release liner was peeled off from the adhesive sheet with release liner (second release liner / adhesive sheet / third release liner). Next, the adhesive sheet exposed by this was attached to a PET film (product name "Lumirror S10", thickness 25 μm, manufactured by Toray) whose surface had been plasma-treated. In the plasma treatment, a plasma irradiation device (product name "AP-TO5", manufactured by Sekisui Kogyo Co., Ltd.) was used, and the voltage was set to 160 V, the frequency to 10 kHz, and the treatment speed to 5000 mm / min (the same applies to the plasma treatment described below). In the bonding, the adhesive sheet was pressed onto the film by moving a 2 kg hand roller back and forth once in an environment of 25°C (the same applies to the bonding described below). Next, the second release liner was peeled off from the adhesive sheet on the PET film. Next, a polyimide (PI) film (product name: Kapton 300V, thickness 75 μm, manufactured by Toray DuPont) with a plasma-treated surface was attached to the exposed adhesive sheet. This resulted in a laminated film (PET film / adhesive sheet / PI film). The laminated film was then autoclaved under conditions of 50°C, 0.5 MPa, and 15 minutes. A rectangular test piece measuring 25 mm x 100 mm was then cut out from the laminated film.
[0126] Next, a bending test was performed on the test piece using a planar body unloaded U-shaped expansion and contraction tester (manufactured by Yuasa System Co., Ltd.). In this test, as shown in FIG. 4A, bending jigs 201 and 202 of the tester were attached to both ends of the long side direction of the test piece 100, respectively, and the test piece 100 was fixed to the tester. Each of the bending jigs 201 and 202 holds a range of 20 mm from the edge of the test piece 100. A central 60 mm area in the long side direction of the test piece 100 is not fixed to the bending jigs 201 and 202. In this test, the test piece 100 was repeatedly deformed (bent) at a bending speed of 60 rpm for a predetermined number of times (e.g., 200,000 times) between a bent form (FIG. 4B) in which the surface on the PI film side is on the outside and a non-bent form (FIG. 4A) in a thermostatic chamber at a temperature of 60° C. and a relative humidity of 95%. In this bending form, the bending radius of the test piece 100 was 1.5 mm, and the bending angle was 180°. The bent portion 100a of the test piece 100 that was repeatedly bent was observed, and the adhesiveness of the adhesive sheet to the adherend in the bending test was evaluated as "good" when no peeling occurred between the adhesive sheet and the adherend (PET film, PI film) after bending 200,000 times or more, evaluated as "fair" when peeling occurred after bending 50,000 times or more and less than 200,000 times, and evaluated as "fail" when peeling occurred after bending less than 50,000 times. The evaluation results are shown in Table 1.
[0127] [Table 1] [Explanation of symbols]
[0128] 10 Adhesive sheet (water-peelable optical adhesive sheet) H Thickness direction 10a 1st end 10b 2nd end 11 Page 1 12 Side 2 21 Acrylic glass plate 22 water L1, L2 Release liner
Claims
1. A water-releasable optical adhesive sheet, Adhesive strength Fw in the first water peel test below 1 is 0.5N / 10mm or less, A water-peelable optically adhesive sheet having an adhesive strength Fz of 1.0 N / 10 mm or more in the following high-temperature, high-humidity peel test. First water peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the water-peelable optical adhesive sheet is bonded to an alkali glass plate prepared by a float method to obtain a first laminate. Next, the first laminate is heated and pressurized at 50° C., 0.5 MPa, and 15 minutes. Next, the first laminate is left to stand at room temperature for 30 minutes. Next, 20 μL of distilled water is supplied onto the alkali glass plate of the first laminate so that the distilled water contacts one end of the adhesive sheet piece in the length direction at the interface between the alkali glass plate and the adhesive sheet piece. Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling the one end of the adhesive sheet piece in the length direction under conditions of 25° C., 50% relative humidity, 180° peeling angle, and 300 mm / min pulling speed, and the adhesive force Fw 1 Measure. High temperature and high humidity peeling test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the water-peelable optical adhesive sheet is attached to an alkali glass plate prepared by a float method to obtain a second laminate. Next, the second laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes. Next, the second laminate is left to stand at room temperature for 30 minutes. Next, the second laminate is subjected to high temperature and high humidity treatment at 60°C, 93% relative humidity, and 15 minutes. Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling one end of the adhesive sheet piece in the length direction under conditions of 60°C, 93% relative humidity, a peel angle of 180°, and a pulling speed of 300 mm / min, to measure the adhesive force Fz.
2. The water-peelable optical adhesive sheet according to claim 1 , having a haze of 1% or less.
3. The water-peelable optical adhesive sheet according to claim 1, which does not peel off even after 200,000 flexions in the following flex test. Flex test: First, a laminated film is prepared in which a polyethylene terephthalate film having a thickness of 25 μm and a polyimide film having a thickness of 75 μm are bonded with the water-peelable optical adhesive sheet. Next, the laminated film is subjected to a heat and pressure treatment under conditions of 50° C., 0.5 MPa, and 15 minutes. Next, a test piece having a width of 25 mm and a length of 100 mm is cut out from the laminated film. Next, in an environment of 60°C temperature and 95% relative humidity, the test piece was bent at the center in the longitudinal direction using a planar body no-load U-shaped expansion and contraction tester under the conditions that the polyimide film side of the test piece was on the outside of the bend, the bending radius was 1.5 mm, the bending angle was 180°, and the bending speed was 60 rpm.
4. The water-peelable optical adhesive sheet according to claim 1 , which has a saturated moisture content of 5% by mass or less at 60° C. and a relative humidity of 95%.
5. In the second water peel test described below, the adhesive strength F 2 and the adhesive force F 1 The adhesive force F 2 The water-peelable optical pressure-sensitive adhesive sheet according to claim 1 , wherein the rate of change of the water-peelable optical pressure-sensitive adhesive sheet is 70% or less. Second water peel test: First, a 10 mm wide x 100 mm long adhesive sheet piece of the water-peelable optical adhesive sheet is attached to an alkali glass plate prepared by a float method to obtain a third laminate. Next, the third laminate is heated and pressurized at 50° C., 0.5 MPa, and 15 minutes. Next, the third laminate is left at room temperature for 72 hours. Next, 20 μL of distilled water is supplied onto the alkali glass plate of the third laminate so that the distilled water contacts one end of the adhesive sheet piece in the length direction at the interface between the alkali glass plate and the adhesive sheet piece. Next, the adhesive sheet piece is peeled off from the alkali glass plate by pulling the one end of the adhesive sheet piece in the length direction under conditions of 25° C., 50% relative humidity, 180° peeling angle, and 300 mm / min pulling speed, and the adhesive force F is measured. 3 Measure.
Citation Information
Patent Citations
Optical adhesive composition and utilization thereof
JP2020023679A